1991
DOI: 10.1002/prep.19910160508
|View full text |Cite
|
Sign up to set email alerts
|

Modeling Hydrodynamic Behaviors in Detonation

Abstract: A multistage reaction model developed for general use from initiation through detonation of heterogeneous high explosives is used to specifically simulate the interface vclocimetry and plate push experiments of a triamino‐trinitrobenzene‐based explosive in detonation. A simplification of the unified model leads to a rate relation that ineludes only two dominant stages: a fast one that represents the major portion of reaction dictated by propagation and decomposition, and a slow one that reflects probably the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1993
1993
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…We have shown in the past that when the BKW EOS is utilized to simulate the aluminum plate push experiments previously described, the calculation overestimates the experiment in later time, indicating a more energetic condition in the low pressure region since this does not happen when a tantalum plate is used (6). Using the new JWL EOS and the reactive burn model, Fig.…”
Section: Products Jwl Equation Of Statementioning
confidence: 87%
“…We have shown in the past that when the BKW EOS is utilized to simulate the aluminum plate push experiments previously described, the calculation overestimates the experiment in later time, indicating a more energetic condition in the low pressure region since this does not happen when a tantalum plate is used (6). Using the new JWL EOS and the reactive burn model, Fig.…”
Section: Products Jwl Equation Of Statementioning
confidence: 87%
“…It is commonly known that the macrokinetics of energy release in detonating HEs with a high content of carbon (e.g., TNT, TATB, and TNT-RDX mixtures) is characterized by two time scales: fast and slow (see, e.g., [10][11][12]). The fast kinetics is related to disintegration of the initial HE molecules and to formation of stable diatomic and triatomic molecules of detonation products and small carbon clusters (10 to 100 atoms).…”
Section: Discussionmentioning
confidence: 99%
“…Frost, the predicted detonation properties and cylinder wall velocities for TATB-based explosives show larger discrepancies with experiment than do the other explosives. Some of these discrepancies are clearly due to nonideal behavior, which has been observed in the effect of diameter on detonation velocity [23] [24] and the effect of charge length on the energy imparted to a target [40] - [42]. Second, the velocity histories of thin plates accelerated by LX 14 also show effects due to the reaction zone [21].…”
Section: Discussionmentioning
confidence: 99%
“…The velocity (or energy) imparted to the target by the explosive is observed to increase with the length of the charge. Tang [42] has shown that these data can be reproduced using a two-step reactive burn model; about 85?40 of the energy is released by a fast reaction, which takes 20 ns, while the rest of the energy is released by a slow reaction that requires an additional 240 ns. The total reaction zone length in Tang's model is about 0.2 cm, which is comparable to the wall thickness in the cylinder tests.…”
Section: Cylinder Test Predictions Using Panda Eosmentioning
confidence: 99%
See 1 more Smart Citation